Weight management and physical activity throughout the cancer care continuum. (22nd November 2017) - Demark‐Wahnefried, Wendy; Schmitz, Kathryn H.; Alfano, Catherine M.; Bail, Jennifer R.; Goodwin, Pamela J.; Thomson, Cynthia A.; Bradley, Don W.; Courneya, Kerry S.; Befort, Christie A.; Denlinger, Crystal S.; Ligibel, Jennifer A.; Dietz, William H.; et al.
Abstract: Mounting evidence suggests that weight management and physical activity (PA) improve overall health and well being, and reduce the risk of morbidity and mortality among cancer survivors. Although many opportunities exist to include weight management and PA in routine cancer care, several barriers remain. This review summarizes key topics addressed in a recent National Academies of Science, Engineering, and Medicine workshop entitled, "Incorporating Weight Management and Physical Activity Throughout the Cancer Care Continuum." Discussions related to body weight and PA among cancer survivors included: 1) current knowledge and gaps related to health outcomes; 2) effective intervention approaches; 3) addressing the needs of diverse populations of cancer survivors; 4) opportunities and challenges of workforce, care coordination, and technologies for program implementation; 5) models of care; and 6) program coverage. While more discoveries are still needed for the provision of optimal weight‐management and PA programs for cancer survivors, obesity and inactivity currently jeopardize their overall health and quality of life. Actionable future directions are presented for research; practice and policy changes required to assure the availability of effective, affordable, and feasible weight management; and PA services for all cancer survivors as a part of their routine cancer care.CA Cancer J Clin 2018;68:64‐89 . ©2017 American Cancer Society .